Thienopyrimidine: A Promising Scaffold to Access Anti-Infective Agents - Prisca Lagardère; Cyril Fersing; Nicolas Masurier; Vincent Lisowski (MDPI AG, 2021)
Thienopyrimidines are widely represented in the literature, mainly due to their structural relationship with purine base such as adenine and guanine. This current review presents three isomers-thieno[2,3-d]pyrimidines, thieno[3,2-d]pyrimidines and thieno[3,4-d]pyrimidines-and their anti-infective properties. Broad-spectrum thienopyrimidines with biological properties such as antibacterial, antifungal, antiparasitic and antiviral inspired us to analyze and compile their structure-activity relationship (SAR) and classify their synthetic pathways. This review explains the main access route to synthesize thienopyrimidines from thiophene derivatives or from pyrimidine analogs. In addition, SAR study and promising anti-infective activity of these scaffolds are summarized in figures and explanatory diagrams. Ligand-receptor interactions were modeled when the biological target was identified and the crystal structure was solved.